Efficacy of technology-based interventions for obesity prevention in adolescents: a systematic review - Chen, Jyu-Lin (Dove Medical Press, 2014)
About one third of adolescents in the USA are overweight and/or obese. Obesity during the adolescent years is associated with many adverse health consequences, including type 2 diabetes, hypertension, hyperlipidemia, and psychosocial problems. Because of substantial advances in technologies and wide acceptance by adolescents, it is now possible to use technology for healthy weight management and prevention of obesity. This systematic review used Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and aimed to evaluate the existing literature reported on the effectiveness of technology-based intervention (web-based, e-learning, and active video games) in preventing obesity in adolescents. The primary aim of this review was to explore if components of specific interventions were associated with a reduction in body mass index. Research articles obtained from CINAHL, Embase, PubMed, PsycInfo, and the Cochrane database from1990 to 2014 were reviewed. A total of 131 published articles were identified, and 14 met the inclusion criteria of a randomized or nonrandomized clinical study with body mass index as primary outcome and/or secondary outcomes of diet/physical activity and/or psychosocial function, tested lifestyle interventions to prevent obesity, used technology, and studied adolescents (aged 12–18 years). The results indicated that six of 14 studies found body mass index and/or body fat decreased at short-term (less than 12 months) follow-up. Six of eleven studies that examined physical activity or physical activity-related outcomes found an improved physical activity outcome (time playing active video games and increase in physical activity time), while five of seven studies which assessed dietary outcomes indicated improvement in dietary behaviors. Five of seven studies suggested an improvement in psychosocial function (reduced depression, improved self-esteem and efficacy, improvement on Behavior Assessment Scale) in adolescents involved in the technology-based intervention. All effective interventions utilized dietary and physical activity strategies as part of intervention components. Because of the variation in duration of intervention (range 10 weeks to 2 years), it is not clear what length of intervention is most effective. Future research should assess the long-term impact of technology-based interventions and evaluate mediators and moderators for weight change in adolescents.